2003
DOI: 10.2223/jped.966
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of factors associated with recurrent and/or severe infections in patients with Down's syndrome

Abstract: Objectives: to evaluate epidemiological, clinical and laboratorial aspects of patients with Down syndrome, who present recurrent and/ or severe infections, as well as to evaluate the presence of immunodeficiency in this population.Methods: patients with Down syndrome diagnosed by chromosome analysis with recurrent and/or severe infections, followed at the Allergy and Immunology Unit of Children's Institute from 1990 to 1999, were submitted to an epidemiological, clinical and laboratorial protocol, including im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 7 publications
(9 reference statements)
1
17
0
Order By: Relevance
“…9,35 In this study, 56.5% of the children presented congenital heart diseases, similar frequency in Brazilian studies, which ranges from 51 to 62.2%. 7,11 The frequencies of types of congenital heart diseases were similar between our study and Ribeiro et al 11 with a greater frequency of interatrial communication in both studies (62% and 46.4%, respectively). In Granzotti et al´s study, 7 frequencies of types of congenital heart diseases differ from those observed in our study.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…9,35 In this study, 56.5% of the children presented congenital heart diseases, similar frequency in Brazilian studies, which ranges from 51 to 62.2%. 7,11 The frequencies of types of congenital heart diseases were similar between our study and Ribeiro et al 11 with a greater frequency of interatrial communication in both studies (62% and 46.4%, respectively). In Granzotti et al´s study, 7 frequencies of types of congenital heart diseases differ from those observed in our study.…”
Section: Discussionsupporting
confidence: 87%
“…However, some characteristics in frequency and severity are variable among the individuals. 5,6,11,29 . The knowledge of clinical manifestations of DS by physicians and other health professionals is important to make an early postnatal diagnosis possible, since prenatal diagnosis is not frequently performed, as in our sample, where all cases were diagnosed in the postnatal period, with diagnostic hypothesis confirmed by cytogenetic analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Down syndrome (DS) is responsible for one third of these [5]. About 9.2% of DS babies do not survive the neonatal period [6], mainly because of associated birth defects [7] and immunodeficiency [8][9][10][11]. We could find only two references in literature regarding the outcome when DS is associated with CDO [12,13].…”
Section: Introductionmentioning
confidence: 99%